2009
DOI: 10.1103/physrevc.79.055203
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic meson form factor from a relativistic coupled-channels approach

Abstract: Point-form relativistic quantum mechanics is used to derive an expression for the electromagnetic form factor of a pseudoscalar meson for spacelike momentum transfers. The elastic scattering of an electron by a confined quark-antiquark pair is treated as a relativistic two-channel problem for the qqe and qqeγ states. With the approximation that the total velocity of the qqe system is conserved at (electromagnetic) interaction vertices this simplifies to an eigenvalue problem for a Bakamjian-Thomas type mass op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(83 citation statements)
references
References 32 publications
5
78
0
Order By: Relevance
“…It was initially applied to calculate the spectrum and decay widths of vector and axial-vector mesons within the chiral constituent quark model [8,9]. Later, electromagnetic properties of spin-0 and spin-1 twobody bound states with equal-constituent masses were studied [10][11][12]. More recently, the relativistic multichannel formalism was extended to unequal-mass constituents and to weak decay form factors in the time-like momentum transfer region [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It was initially applied to calculate the spectrum and decay widths of vector and axial-vector mesons within the chiral constituent quark model [8,9]. Later, electromagnetic properties of spin-0 and spin-1 twobody bound states with equal-constituent masses were studied [10][11][12]. More recently, the relativistic multichannel formalism was extended to unequal-mass constituents and to weak decay form factors in the time-like momentum transfer region [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…If M is a pseudoscalar meson it can be shown that [6,7]. Since internal momenta are integrated over, the most general covariant decomposition of J µ em thus takes on the form…”
Section: Relativistic Multichannel Formalism and Hadron Currentsmentioning
confidence: 99%
“…"On-shell" means that (2) and the explicit expression for the meson current J µ em (k ′ M ; k M ) in terms of the constituent currents and the bound-state wave functions are given in Refs. [6,7,8].…”
Section: Relativistic Multichannel Formalism and Hadron Currentsmentioning
confidence: 99%
See 2 more Smart Citations